Remote, tablet-based assessment of gaze following: a nationwide infant twin study - Shic, Frederick; Dommer, Kelsey Jackson; Benton, Jessica; Li, Beibin; Snider, James C.; Nyström, Par; Falck-Ytter, Terje (Frontiers in Psychology, 2023)
Much of our understanding of infant psychological development relies on in-person, lab-based assessment. This limits research generalizability, scalability, and equity in access. One solution is the development of new, remotely deployed assessment tools which don’t require real-time experimenter supervision. The current nationwide (Sweden) infant twin study assessed participants remotely via their caregiver’s tablets (N = 104, ages 3- to 17-months). To anchor our findings in previous research, we used a gaze following task where experimental and age effects have been well-established. Closely mimicking results from conventional eye tracking, we found that seeing a full head movement elicited more gaze following than seeing isolated eye movements. Further, as expected, we found that older infants followed gaze more frequently than younger infants. Finally, while we found no indication of genetic contributions to gaze following accuracy, latency to disengage from gaze cue and orient towards a target was significantly more similar in monozygotic twins than dizygotic twins, indicative of heritability. Together, these results highlight the potential of remote assessment of infants’ psychological development, which can improve generalizability, inclusion and scalability in developmental research.